From Darwinian Metaphysics towards Understanding the Evolution of Evolutionary Mechanisms - A Historical and Philosophical Analysis of Gene-Darwinism and Universal Darwinism - von Sydow ,Momme (Universitèatsverlag Gèottingen, 2012)
Although Charles Darwin predicted that his theory